2020
DOI: 10.5397/cise.2020.00080
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral acromial stress fractures in a patient with a massive rotator cuff tear

Abstract: Stress fractures of the acromion and scapular spine are well-known complications following reverse total shoulder arthroplasty. However, these fractures in patients with massive rotator cuff tear or cuff tear arthropathy are extremely rare, and the pathogenesis, clinical features, diagnosis, and treatment of these fractures are poorly understood. We report a case of bilateral stress fracture of the posterior angle of the acromion in a patient with massive rotator cuff tear and discuss the pathogenesis, clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Three studies were excluded as the specific treatment for acromial/scapular spine fracture was not mentioned [ 21 , 22 , 23 ]. Three studies did not report on acromial/scapular spine fracture in the context of RSA, one study was not in German or English language, and one study did not report on specific outcomes after treatment of acromial/scapular spine fracture [ 24 , 25 , 26 , 27 , 28 ]. One study was identified from review references of the identified articles [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three studies were excluded as the specific treatment for acromial/scapular spine fracture was not mentioned [ 21 , 22 , 23 ]. Three studies did not report on acromial/scapular spine fracture in the context of RSA, one study was not in German or English language, and one study did not report on specific outcomes after treatment of acromial/scapular spine fracture [ 24 , 25 , 26 , 27 , 28 ]. One study was identified from review references of the identified articles [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…A considerable proportion of patients (65.7%) with rotator cuff tears had SD. Although the cause‐and‐effect relationship between SD and shoulder pathologies remains uncertain, and SD may have had variable etiologies [17, 27], the increased risk of external and internal impingements by SD may create a condition wherein rotator cuff tears can easily develop [6, 32]. As previously reported [16], the mean increases in UR, anterior tilt, and IR were also found in this study compared with the intact contralateral scapula in patients with rotator cuff tears.…”
Section: Discussionmentioning
confidence: 99%